Clinical Features and Severity of Leptospirosis Cases Reported in the Hawke's Bay Region of New Zealand. (8th July 2021) - Sellors, Paul; Watson, Rebecca F.; Bate, Rachel; Bentham, Gemma L.; Haigh, Kathryn
Abstract : Aims . To record demographics, symptoms, signs, and laboratory features of confirmed leptospirosis cases in the Hawke's Bay area of New Zealand to aid clinicians in diagnosis and recognition of severity. Methods . Review of suspected leptospirosis cases referred to the reference laboratory from hospitals in the Hawke's Bay region between March 2003 and March 2012. Inclusion criteria were IgM positivity and diagnosis confirmed with either polymerase chain reaction (PCR) or microscopic agglutination test (MAT). A retrospective systematic review of case notes was completed for demographic and laboratory data. Results . Forty-three cases were included. Most common presenting symptoms were pyrexia (93%), myalgia, and headache (both 86%). 93% of patients worked in the farming or meat industries. The most common biochemical abnormalities were elevated CRP (100%) and abnormal urinalysis (93%). There was no difference in disease severity between icteric and anicteric patients. Compared to other studies, patients in New Zealand have less severe disease. Conclusion . Contrary to popular understanding, this study has not found icteric leptospirosis to be related to more severe disease. Anicteric leptospirosis should be a differential diagnosis in patients presenting with pyrexia, myalgia, and headache who have elevated CRP and abnormal urinalysis.